(untitled) (Journal of The Colloquium for Information Systems Security Education, 2023)
Cybersecurity is an interdisciplinary field that is concerned with protecting digital assets from cyber-attacks aiming to illegally access sensitive information in order to tamper and disrupt systems and processes. Producing cybersecurity materials that are vertically-aligned is highly desired, given the shortage of cybersecurity educators and the dynamic and evolving nature of cybersecurity. More specifically, universities must do more to help fill the huge cybersecurity workforce shortage and address the lack of materials centered around adversarial thinking. In this paper, we propose a four-step process to turn a recent cybersecurity paper into a hands-on lab that utilizes game theory to promote adversarial thinking and show a case study where this process was used. The four-step process explains how papers are chosen, their research replicated, the production of lab materials, and complementary materials for students to work from. The case study demonstrates this process in practice and explains how game theory is incorporated into the lab.